Abnormalities of thyroid function tests in adult patients with nephrotic syndrome - Karethimmaiah, Hareeshababu; Sarathi, Vijaya (International Journal of Research in Medical Sciences, 2016)
Background: Nephrotic syndrome is well-known cause of thyroid dysfunction in children; however, there is limited data on this issue in adults, especially regarding natural course of thyroid abnormalities. Methods: Patients with nondiabetic nephropathies were included in the study and evaluated with thyroid function tests at diagnosis and every 2-3 monthly. Age and sex matched healthy volunteers constituted the control group. Results: The study included 39 patients with newly diagnosed nephrotic syndrome and 39 controls. When compared to the control group, patients with nephrotic syndrome had significantly higher thyroid stimulating hormone and significantly lower total thyroxine, total triiodothyronine, free thyroxine and free triiodothyronine levels. Eighteen patients had remission at last follow-up (18.3±3.4 months) and those with remission had improvement in thyroid function tests. Anti thyroperoxidase antibody tended to be more common in nephrotic syndrome patients and among patients with remission, elevated antibodies was associated with persistence of hypothyroidism. Conclusions: Nephrotic syndrome in adult patients is significantly associated with abnormalities in thyroid function tests. All these abnormalities improve with remission of nephrotic syndrome. Patients with elevated thyroid stimulating hormone and anti-thyroperoxidase antibody levels are more likely to progress to overt hypothyroidism and should be closely followed-up or replaced with levothyroxine.